(untitled) (Research, Society and Development, 2021)
This study aimed to highlight the contributions of international exchanges in the training and performance of nurses through the academic, professional and postgraduate levels. This is an integrative review carried out from July to September 2020 in the PubMed, LILACS, Cochrane and Scielo databases. The selection of studies by title and abstracts and by complete reading was carried out by two reviewers independently. The studies that generated some disagreement among the reviewers regarding the inclusion were discussed with a third reviewer. The filtering process resulted in 49 articles on international exchanges, of which, 75.5% were academic exchanges, 16.3% were graduate students in nursing and 8.2% were professionally trained. During the analysis of the theoretical frameworks involved in this study, it was noticed in all areas of training, both academic and professional, that international mobility develops in the participant’s scientific technical knowledge, adding efficiency to professional practices, in addition to strong personal development. It is concluded that internationalization in nursing is a potential differential for nurses, whether they are still in their training process, as a graduate student or as a postgraduate student, both having the opportunity to study and experience other teaching methodologies, and even to know and carry out nursing practices in a country other than the country of origin, improving their professional skills.